Supply Chain Operational Capability and Supply Chain Operational Performance: Does the Supply Chain Management and Supply Chain Integration Matters? - Saragih, Jopinus; Tarigan, Adrian; Frida Silalahi, Elba; Wardati, Jumadiah; Pratama, Ikbar (International Journal of Supply Chain Management, 2020)
The aim of the study is to recognize the pattern of the interactive association between SC operational capability and corporate competitive capability for improving performance. Moreover, the study is based on analyzing the influence of SC integration on the interactive relation as a strategic lever. There is a need to consider potential implications of efficient relation between SC operational capability and corporate competitive capability to develop integrated and coherent strategies for the strategic role of SCM. The decisions linked with the sourcing of products, planning capacity, conversion into final products, distribution, communication, demand management, and delivery is regarded as SC operational capability. The study has opted the SEM-PLS for the analysis of the data, which is among the most recent and robust data analysis technique especially for the structural issues in social sciences. The data is collected with the aid of a questionnaire which was developed basing on the prior studies. It has been stressed by previous studies on manufacturing strategy and SCM that the decisions of SCM must be aligned and strategic with the business strategy of the firm. However, consistent results have not revealed by previous literature about the shape of the interactive association between SCM strategy and corporate strategy. There are several implications of this study for theory developers and academicians. The previous frameworks of supply chain practices based on the context of developed countries have been extended by this research by incorporating various dimensions of SCI practices in the context of a developing country. The study has focused on manufacturing firms in Indonesia.